(untitled) (Journal of Educational Sciences, 2017)
The article describes the aims and tasks of the discipline, structural and content system of the “Self-cognition” course in higher educational institutions. And also the article examines the contents of the discipline in conjunction with the contents of other humanitarian, social, public disciplines, it is specified that it will be integrated with the basis of the spiritual and moral education which are necessary for self-cognition of student. Author wrote that with self-cognition the students will be have skills to help each other, live in harmony with themselves, treated with respect to closes, to be sincerely in minds, words, acts, be actively, be responsible for the manifestation of citizenship and patriotism. The author revealed three conditions of learning self-cognition like as create an atmosphere of faith in love, inspiration, to create conditions for intuitive self-realization; integrate learning spiritual-moral education and full pedagogical process; needs in using positive methods in learning process.